Analisis Diksi pada Teks Laporan Hasil Observasi Buku Ajar Siswa Bahasa Indonesia SMP Kelas VIII - Nurul Lailatuz Zakiyah; Fitri Sakinah; Mar’atus Sholihah; Laylatul Musoffa; Mohamad Afrizal (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This study aims to describe and analyze various forms of lexical errors found in the observation report texts in Indonesian language textbooks for eighth-grade junior high school students, as well as identify inappropriate diction based on categories such as connotative, denotative, formal, informal, general, specific, and borrowed foreign words. The research utilized a qualitative descriptive linguistic analysis of three authentic and representative observation report texts. The findings indicate numerous lexical errors, including the use of foreign terms without equivalents, redundant synonyms, and words inappropriate for formal or scientific contexts. These errors potentially reduce communication effectiveness, disrupt message clarity, and affect language correctness within the texts. If left uncorrected, such errors may cause ambiguities and hinder students’ comprehension of the reports objectively and accurately. Suggested corrections include selecting precise, specific words aligned with Indonesian language norms and employing neutral, objective language to facilitate student understanding and strengthen the educational value of the textbook. These findings provide valuable references for developing quality teaching materials and enhancing teachers’ and authors’ competencies in crafting effective, standards-compliant texts. This research is expected to offer practical and theoretical benefits, ultimately improving the overall language learning process in educational settings.